Fluorescent Switchable Surfaces Based on Quantum Dots Modified With Redox‐Active Molecules - Campos‐Lendinez, Ángel; Muñoz, Jose; Crivillers, Núria; Mas‐Torrent, Marta (Advanced optical materials, 2024)
By combining the switching ability of redox molecules with the unique fluorescence properties of quantum dots (QDs), a robust electrochemical fluorescence switch is developed here. This is realized by grafting CdSe/ZnS QDs on transparent indium tin oxide (ITO) substrates and, subsequently, modifying them with a Ferrocene (Fc) molecular monolayer. The application of oxidation/reduction voltage pulses to tune the Fc redox state leads to the tuning of the surface fluorescence output. Interestingly, the ON/OF ratio can be enhanced by reducing the distance between the redox active unit and the QD due to a more efficient electronic coupling. Remarkably, by defining a mixed‐valence state, a ternary switch has also been achieved. It is highlighted that the QD surface immobilization is key to realize this switch to avoid aggregation and fluorescence quenching in suspension. Hence, an efficient and versatile novel route to fabricate robust fluorescent redox switches is demonstrated, opening a wide avenue of possibilities to be explored in the field of sensing and information storage. A robust electrochemical fluorescence switch is realized by grafting CdSe/ZnS Quantum Dots on transparent indium tin oxide (ITO) substrates and, subsequently, modifying them with a Ferrocene (Fc) molecular monolayer. The application of oxidation/reduction voltage pulses to tune the Fc redox state leads to the tuning of the surface fluorescence output.